2014
DOI: 10.3906/bot-1403-87
|View full text |Cite
|
Sign up to set email alerts
|

The Colchic region as refuge for relict tree lineages: cryptic speciation in field maples

Abstract: IntroductionThe genus Acer is the second-largest tree genus in the northern hemisphere in terms of the number of accepted species (van Gelderen et al., 1994;de Jong, 2002). Intrageneric classifications of the genus based on morphology and chemotaxonomy have been unstable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 49 publications
11
33
0
Order By: Relevance
“…To assess whether R. alpina was historically closely associated with its hosts, we compared the phylogeographical patterns of R. alpina to those of its marginal hosts ( Fraxinus , Ulmus , Acer, and Tilia ) and the main host ( Fagus sylvatica s.l.). Even though information about some of the marginal hosts is rather fragmentary, some basic patterns can be inferred (Grimm & Denk, ; Heuertz et al., ; Myking & Yakovlev, ; Phuekvilai, ; Whiteley, ). Unlike R. alpina , the marginal hosts consist of several genetically diversified lineages surviving in multiple refugia throughout Europe.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether R. alpina was historically closely associated with its hosts, we compared the phylogeographical patterns of R. alpina to those of its marginal hosts ( Fraxinus , Ulmus , Acer, and Tilia ) and the main host ( Fagus sylvatica s.l.). Even though information about some of the marginal hosts is rather fragmentary, some basic patterns can be inferred (Grimm & Denk, ; Heuertz et al., ; Myking & Yakovlev, ; Phuekvilai, ; Whiteley, ). Unlike R. alpina , the marginal hosts consist of several genetically diversified lineages surviving in multiple refugia throughout Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Acer is still quite diverse in the flora of western Eurasia with ca. 17 species in three sections (van Gelderen et al 1994;Grimm et al 2007;Grimm and Denk 2014).…”
Section: Speciation and Extinction In The Late Pliocene Of Europementioning
confidence: 99%
“…In recent classifications, Acer consists of 16 sections and 126 species (Acevedo-Rodringuez et al 2011). There are so high hybridization and diversity between Acer species that taxonomic identification is difficult (Grimm et al 2007(Grimm et al , 2014. Interand intraspecific variability of the group is the main cause of its taxonomic complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with hybridization as a potentially effective phenomenon in the formation of species complexes, it is difficult to identify species of maples (Grimm et al 2007). Characterizing the new sequence types, Grimm and Denk (2014) showed that cryptic speciation can occur in isolated populations of B I O D I V E R S I T A S 20 (1): 297-304, January 2019 298 maples and reported cryptic species in maples from Georgia. Cytogenetic studies of Acer, which has a basic chromosome number of 13 (x = 13) and various levels of ploidy (Grimm and Denk 2014), confirms inter-and intraspecific complications in the genus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation